Customer Loyalty through Satisfaction in Bank Jago: A TAM Based Approach with Trust, Security, and Risk Perceptions - Jauza Audy Safitri; Ghea Sekar Palupi (Journal of Emerging Information Systems and Business Intelligence (JEISBI), 2026)
The rapid growth of digital banking services has encouraged users to shift toward applications that offer convenience and efficiency, such as Bank Jago. However, the account breach incident in July 2024 raised concerns about application security and potentially affected customer satisfaction and loyalty. This study aims to analyze the factors influencing customer satisfaction and their impact on customer loyalty in the Bank Jago application. The research model adopts the Technology Acceptance Model (TAM), incorporating core constructs—Perceived Ease of Use (PEOU) and Perceived Usefulness (PU)—along with additional variables: Perceived Trust (PT), Perceived Security (PS), and Perceived Risk (PR). Customer Satisfaction (CS) serves as the mediating variable, while Customer Loyalty (CL) is the dependent variable. Data were collected from 238 respondents and analyzed using Structural Equation Modeling (SEM) with SmartPLS. The results show that PEOU, PU, and PT have a positive and significant influence on CS, whereas PS and PR do not have a significant effect. Furthermore, CS has a positive and significant influence on CL. These findings highlight the extended TAM framework in explaining digital banking behavior and emphasize the crucial role of user satisfaction in driving customer loyalty.